Pengaruh Defoliasi Daun dan Subtitusi Pupuk NPK Phonska dengan Guano terhadap Produksi Jagung (Zea mays L.) - Novitasari, Vrida; Soedjarwo, Djarwatiningsih Poengky; Suhardjono, Hadi (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Corn (Zea mays L.) is the most essential food commodity after rice and a secondary crop. The demand for Corn in Indonesia is currently relatively high, yet its production has been declining. To increase Corn production, improvements in cultivation techniques are necessary. One such method is optimizing assimilate distribution through leaf defoliation, as well as creating optimal growing conditions through fertilization. Fertilization should be balanced by using both inorganic and organic fertilizers. In this study, NPK Phonska and Guano fertilizers were used. Methods: This study employed a factorial randomized complete block design (RCBD) with two factors. The first factor was the level of leaf defoliation below the cob, consisting of three levels: no defoliation (D1), defoliation leaving three leaves (D2), and defoliation leaving two leaves (D3). The second factor was the substitution of NPK Phonska and guano fertilizers with five levels: 100% NPK Phonska (P1), 75% NPK Phonska + 25% Guano (P2), 50% NPK Phonska + 50% Guano (P3), 25% NPK Phonska + 75% Guano (P4), and 100% Guano (P5). Results: The study's results showed that defoliation, leaving two leaves below the cob, combined with the application of 7 tons/ha of guano fertilizer without the addition of NPK, increased cob weight, cob length, and dry kernel weight per plant. Additionally, the independent application of 7 tons/ha of guano fertilizer without NPK Phonska significantly increased cob diameter. Conclusions: The combination treatment of defoliation, leaving two leaves below the cob, and the application of 7 tons/ha of guano fertilizer without the addition of NPK had the most favorable effect on Corn production.